2017
DOI: 10.1002/etep.2357
|View full text |Cite
|
Sign up to set email alerts
|

Design and manufacturing of a single-phase induction motor: A decision aid tool approach

Abstract: Summary This paper presents a simple, practical, and effective design, analysis, and selection approach of a capacitor‐run single phase induction motor as a manufacturing aid tool at the early stage of the design. The standard industrial motor frame sizes as well as the current design trends of larger lengths and smaller diameters—which are not likely presented in literature—are taken into account. At first, to verify the proposed approach, a sample single phase induction motor design is obtained regarding cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It was mentioned that the preliminary results of an author's recent work 31 indicated that the increment of the SPIM's axial effective length benefits the motor's efficiency toward IE3 standards. However, the improved efficiency has to be combined with the satisfaction of many other requirements (eg, adequate starting torque, low starting current, current density, and so on) aiming the SPIMs to comply with the latest international industrial standards.…”
Section: Description Of the Examined Design Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was mentioned that the preliminary results of an author's recent work 31 indicated that the increment of the SPIM's axial effective length benefits the motor's efficiency toward IE3 standards. However, the improved efficiency has to be combined with the satisfaction of many other requirements (eg, adequate starting torque, low starting current, current density, and so on) aiming the SPIMs to comply with the latest international industrial standards.…”
Section: Description Of the Examined Design Methodsmentioning
confidence: 99%
“…They claim that their efficiency cannot be enhanced over the ordinary ratings and thus it will be difficult for them to exhibit an efficiency of IE3 according to the latest industrial standards 30 . On the other hand, the preliminary results of an authors' recent research effort (ie, Reference 31) indicate that the capacitor‐run SPIM's axial effective length increment along with the incorporation of die‐cast copper squirrel‐cages benefits its efficiency toward IE3. The SPIMs topologies (developed in Reference 31) presented the desirable efficiency, but not adequate starting torque.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case when the number of rotor bars is a divisor of 2p(mz+1), lower RSHs exist in the stator current spectrum at frequencies given by (9) and associated lower pulsating torque components at frequencies given by (11).…”
Section: Optimal Number Of Rotor Bar Selectionmentioning
confidence: 99%
“…A centrifugal switch (S) is arranged to remove this capacitor once the machine attains full speed. A run capacitor (usually of less value than the start capacitor) is left in the auxiliary winding, as it allows the motor to develop higher running torque, greater efficiency, and improved power factor . The specifications of the machine to be studied are given in Table .…”
Section: Modeling Of Dol‐synrmmentioning
confidence: 99%